Synthesis of poly aluminium chloride (PAC) from aluminum cable waste through the polymerization process - Gemilang, Surya; Athobarani, Akmal; Sari, Ni Ketut; Lestari, Rowina (Konversi, 2024)
Cable waste is classified as inorganic waste that is difficult to decompose. Aluminum cable waste has good coagulant properties if it can be synthesized into Poly Aluminium Chloride (PAC) because the active aluminate groups can aggregate suspended materials in water into flocks during the coagulation-flocculation process in water purification. PAC is made by hydrolyzing aluminum samples with a 33% HCl solution. The sample is then left for one day to complete the hydrolysis process. After the formation of the AlCl3 solution, polymerization is carried out by adding a Na2CO3 solution. In the research conducted, the best result was a turbidity reduction value of up to 2.96 NTU with the addition of 30 ml of AlCl3 monomer and a Na2CO3 initiator with a concentration of 7N. After optimization using Response Surface Methodology (RSM) in the Design Expert 13 software, the most optimal result for the synthesized PAC was found to reduce wastewater turbidity to 2.609 NTU with variables of 25.992 ml of AlCl3 monomer volume and 5.248N of Na2CO3 initiator concentration. Based on this research, the concentration of the initiator has a significant effect on the ability of the monomer to bind into a PAC polimer chain.